Dandy-Walker Syndrome. Case Report and Literature Review - William Ernesto González Águila; Osiris Intento García; Nilda Beatriz Cortizo Martínez (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Dandy-Walker syndrome is associated with cystic dilatation of the fourth ventricle, varying degrees of abnormality of the cerebellar vermix, and supratentorial hydrocephalus. It is mainly based on an abnormal development of the cerebrospinal fluid communication pathways. Genetic predisposition associated with malformations and chromosomal alterations has been suggested. The diagnosis can be carried out during the prenatal or postnatal stage, clinically and diagnostic imaging studies. We present the case of a newborn who was admitted to the Neonatal Intensive Care Unit due to hypotonic, tongue protrusion with sucking disorders. A transfontanellar ultrasound was performed, with dilation of the lateral ventricles. In addition to the dilation of the lateral ventricles, a cyst in the choroid plexus and signs of brain atrophy were observed. She was diagnosed with Dandy-Walker syndrome, without surgical criteria because she did not present signs of hydrocephalus. The case is presented because it is a rare malformation of the central nervous system.